The effect of the different spacing ratios on wave energy converter of three floating bodies. (1st April 2023) - Li, Boyang; Li, Canpeng; Zhang, Baoshou; Deng, Fang; Yang, Hualin
Abstract: In this paper, a spring-mounted floating body was numerically investigated with 2-dimensional simulations to examine the effects of distance between floating bodies on the energy conversion. The average amplitude, average power and energy conversion efficiency of the three floating bodies are discussed separately at the end of the paper. With the increase of distance, the interaction between floating bodies gradually becomes smaller, where the average power of each floating body is similar, when the spacing ratio is 7 (the actual distance is 2.1 m). It is found that the interaction between floating bodies is not always negative for the conversion of energy, when the distance is small. The power of the floating body increases with the increase of the wave height. When the wave height and the diameter of the floating body (D = 0.3 m) are close, the slope of the amplitude curve and power curve of the floating body is the largest, and the energy conversion efficiency is optimal. After the wave height exceeds the diameter of the float, the power and conversion efficiency of the floating body will tend to decrease as the wave height increases.